Answer:
Explanation:
Remark
You are going to use the Pythagorean Theorem. The trick is to find the length of the leg making up the base of the triangle.
That base is equal to the difference between the two bases.
Solution
The base of the triangle = 2x + 1 - (x + 3) Remove the brackets.
base = 2x + 1 - x - 3
base = x - 2
Now the height of the trapezoid is also the second leg of the triangle. Apply the Pythagorean Theorem.
c^2 = a^2 + b^2
a = x - 2
b = x + 4
c = 2x
4x^2 = (x - 2)^2 + (x + 4)^2 Expand the brackets
4x^2 = x^2 - 4x + 4 + x^2 + 8x + 16 Collect like terms
4x^2 = 2x^2 + 4x + 20 Subtract the right side from the left.
4x^2 - 2x^2 - 4x - 20 = 0
2x^2 - 4x - 20 = 0 Divide by 2
2x^2/2 - 4x/2 - 20/2 = 0
x^2 - 2x - 10 = 0
x = - b +/- sqrt(b^2 - 4*a*c)/ 2a
a = 1
b = - 2
c = - 10
x = (- -2 + / - sqrt((-2)^2 - 4*(1)*(-10) ) / 2
x = (2 + / - sqrt(4 + 40 ))/2 Only the plus root has any meaning.
x = ( 2 + sqrt(44 ) )/2
x = ( 2 + 2*sqrt(11) ) / 2
x = 1 + sqrt(11)
sqrt(11) = 3.3166
x = 1 + 3.3166
x = 4.3166